2018
DOI: 10.3390/ijerph15061218
|View full text |Cite
|
Sign up to set email alerts
|

Factors Correlated with Success Rate of Outpatient Smoking Cessation Services in Taiwan

Abstract: Smoking is the leading cause of preventable death. The purpose of this study was to explore the patient’s and physician’s factors that are correlated with smoking cessation success rate. A total of 877 smokers who visited the outpatient smoking cessation services at a medical center in Northern Taiwan were recruited for the study. Phone interviews were carried out six months after the initial visit to evaluate the success rate of smoking cessation. The result showed that the abstinence rate at six-month was 37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 21 publications
2
26
0
Order By: Relevance
“…Research in Turkey detected higher rates of quitting smoking in patients who attended in three months one or more follow-up sessions, and even higher for three or more follow-up sessions 23 . A recent international study reported smokers who had more than one smoking cessation follow-up visit or were seen by a physician had a higher success rate 24 . Research has noted that the use of pharmacotherapy for at least five weeks was associated with an increased smoking cessation rate 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Research in Turkey detected higher rates of quitting smoking in patients who attended in three months one or more follow-up sessions, and even higher for three or more follow-up sessions 23 . A recent international study reported smokers who had more than one smoking cessation follow-up visit or were seen by a physician had a higher success rate 24 . Research has noted that the use of pharmacotherapy for at least five weeks was associated with an increased smoking cessation rate 15 .…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional study in rural Andhra Pradesh, India, the smoking rate among men was significantly higher (50.3%) than among women (4.8%), but the SC rate among women (45.5%) was significantly higher than that among men (18.8%) In this study, univariate analysis showed no statistically significant difference between age bracket and success rate of SC. Some studies have suggested that age is a factor in the success of quitting, while others have found the opposite (21,(47)(48)(49). Further research is needed to determine the role of age as a factor in SC success.…”
Section: Characteristics Of Sc Participantsmentioning
confidence: 98%
“…This relationship may be related to a healthy-worker-like effect, where it has been observed that workers typically exhibit lower overall death rates as compared to the general population because the severely ill and disabled are unable to work. In addition, smokers may change lifestyle when they suffer from diseases or are more aware of the harmful effects of smoking [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%